Trends of Antihypertensive, Antidiabetic, and Nonsteroidal Anti-Inflammatory Drugs Use among the Health Workers Cohort Study, Mexico 2004 to 2018 - Janinne Ortega-Montiel; Alejandra Montoya; René Soria-Saucedo; Katia Gallegos-Carrillo; Paula Ramírez-Palacios; Jorge Salmerón; Eduardo Salazar-Martínez (Hindawi Limited, 2023)
Background. Hypertension and type 2 diabetes (T2D) are the most prevalent noncommunicable diseases in Mexico and worldwide. According to international practice management guidelines, the principal chronic management therapy is daily oral medication. Aim. We aim to describe the trends of antihypertensive, antidiabetic, and nonsteroidal anti-inflammatory (NSAID) drugs use among the Mexican adult population from 2004-2018. Methods. We analyzed data from the Health Workers Cohort Study (HWCS) for males and females aged >18 years. We calculated the prevalence of chronic diseases and utilization for every kind of antihypertensive, antidiabetic, and NSAIDs (measured by self-reported utilization) at baseline and two follow-ups (2004, 2010, and 2017). Trends were analyzed using Fisher's exact test. Results. Hypertension prevalence increased from 19.8 to 30.3%, higher than T2D prevalence from 7.0 to 12.8% through fourteen years of follow-up. Like the self-reported dual therapy, the proportion of patients using beta-blockers and angiotensin II receptor blockers increased. Regarding T2D, the prevalence of metformin utilization increased to 83.9%. The utilization of common NSAIDs, mainly for muscular pain, remained around 13 to 16%. Conclusions. Our findings showed a changing prevalence of drug utilization for hypertension and T2D between 2004 and 2018 and consistent use of NSAIDs in the adult Mexican population.